Simplify (14x2−3x+2.25)+(0.75x2+2x−14)

1 answer

To simplify the expression \((14x^2 - 3x + 2.25) + (0.75x^2 + 2x - 14)\), we combine like terms.

  1. Combine the \(x^2\) terms:

    \[ 14x^2 + 0.75x^2 = 14.75x^2 \]

  2. Combine the \(x\) terms:

    \[ -3x + 2x = -1x \quad \text{(or simply -x)} \]

  3. Combine the constant terms:

    \[ 2.25 - 14 = 2.25 - 14 = -11.75 \]

Now, putting it all together:

\[ (14x^2 - 3x + 2.25) + (0.75x^2 + 2x - 14) = 14.75x^2 - x - 11.75 \]

Thus, the simplified expression is:

\[ \boxed{14.75x^2 - x - 11.75} \]